1
You visited us 1 times! Enjoying our articles? Unlock Full Access!
Question

# Solve the following pair of equations. 5x−1+1y−2=2 6x−1−3y−2=1 Here, x ≠ 1 and y ≠ 2

A

x = 4, y = 5

Right on! Give the BNAT exam to get a 100% scholarship for BYJUS courses
B

x = 5, y = 3

No worries! We‘ve got your back. Try BYJU‘S free classes today!
C

x=13, y=13

No worries! We‘ve got your back. Try BYJU‘S free classes today!
D

x = 7, y = 11

No worries! We‘ve got your back. Try BYJU‘S free classes today!
Open in App
Solution

## The correct option is A x = 4, y = 5 If we substitute 1x−1 as p and 1y−2 as q in the given equations, we get the equations as 5p+q=2 .......(1) 6q−3q=1 .......(2) Now, we can solve the pair of equations by method of elimination. On multiplying the first equation by 3 and then adding it to (2), we get 15p+3q=6 6p−3q=1 _____________ p=13 Now by substituting the value of p in equation (2) we get q=13 Now, p=1x−1 ⇒1x−1=13 ⇒x=4 Similarly we assumed q=1y−2 ⇒1y−2=13 ⇒y−2=3 ⇒y=5 ∴x=4 and y=5

Suggest Corrections
0
Join BYJU'S Learning Program
Related Videos
Solving Linear Equations
MATHEMATICS
Watch in App
Join BYJU'S Learning Program